Spatial transformation: An introduction to the Great Transformation towards sustainability - Martin Held (Spatial transformation: Processes, strategies, research design, 2022)
A Great Transformation from fossil-based unsustainability to post-fossil sustainable development is on the horizon. This article provides an introduction to the research and debate on the sustainability transformation, with a special focus on the spatial dimension. Examples of current approaches and research are presented. Spatially orientated transformation research requires a view of the temporal processes.
urn:nbn:de:0156-08910384; hdl:10419/251347; https://econpapers.repec.org/RePEc:zbw:arlfob:19
Keywords: 710; Great transformation; unsustainability; sustainable development; spatial transformation; transformation approaches; timescapes; landscapes; digital transformation